Toward an Integrative Prophetic Leadership Model in Education: Evidence from an Extended Ethnographic Study - Akhmad Fauzi Hamzah; Ahmad Qusairi; Muhamad Maulana; Ikmal Wahyudi (Journal of Educational Management Research, 2026)
This study aims to examine how prophetic leadership is constructed and practiced within the socio-cultural dynamics of Islamic boarding schools and to develop an integrative conceptual framework based on empirical evidence. A qualitative research design with an extended ethnographic approach was employed, with data collected through participatory observation, in-depth interviews, and document analysis involving leaders, teachers, senior students, and administrative staff, and analyzed using thematic coding. The findings reveal that prophetic leadership is manifested through four interrelated dimensions: spiritual legitimacy, exemplary behavior, transformational negotiation, and cultural reproduction. Spiritual legitimacy is constructed through collective religious validation, while exemplary behavior functions as a medium of moral socialization within the institutional community. In addition, leaders continuously negotiate between traditional religious values and organizational transformation demands. This study proposes an integrative framework in which spirituality is positioned not merely as a moral foundation but as an active instrument of leadership practice. Theoretically, the study contributes to leadership scholarship by offering a context-sensitive model of spiritual leadership, while practically it provides insights for strengthening leadership strategies in faith-based educational institutions.